Chemical Characterization of Moringa oleifera Lam. from Six Growth Locations in Central of Java: An Initiation of Standardization `: Karakterisasi Kimia Moringa oleifera Lam. dari Enam Lokasi Tumbuh di Jawa Tengah: Inisiasi Standardisasi - Budiarti, Mery; Wijaya, Nur Rahmawati; Jokopriyambodo, Wahyu (Jurnal Tumbuhan Obat Indonesia, 2024)
Moringa oleifera Lam. is in high demand as a raw material for pharmaceutical constituents and dietary supplements, particularly for producing stunting supplements. However, recommendations regarding M. oleifera quality standards have not supported this claim as scientific evidence of its safety and effectiveness. This research intends to expand knowledge regarding the quality standards of M. oleifera leaves, particularly their chemical properties. Height-variant samples of M. oleifera were collected from six locations in the Central Java, Indonesia. A hierarchical cluster analysis (HCA) was performed to group the most each parameter's values. The parameters included water-soluble extract, ethanol-soluble extract, total ash content, acid-insoluble ash, total flavonoid content was quantified as quercetin, and thin-layer chromatography (TLC) fingerprint. The suggestion of specific value for each parameter as a future reference for M. oleifera, including water- and ethanol-soluble extract content of at least 41% and 19%, and a total- and acid-insoluble ash content of a maximum of 11% and 4%, respectively. The minimal quercetin contains as the chemical marker compound of M. oleifera was a minimum of 1.285%. The chromatogram profile of TLC suggested 7 (254 nm) and 8 (366 nm) spots.